EWA WUNA TRADITIONAL SPORT OF SOUTHEAST SULAWESI - Sawali, La (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
The trend of reviving traditional sports to restore the position of Indonesian national identity is a phenomenon that must continue to be explored.  Academicians and sports practitioners are responsible for this. Ewa Wuna 's traditional sport at Southeast Sulawesi is one of the options that should be considered by folk sports of Southeast Sulawesi, related to the intelectual development of the younger generation and the attitude of Nationalism that must be maintained. The pattern of a descriptive qualitative method by looking at the potential of traditional sports for the interests of the integrity of the nation was developed in this article. The consideration of intra-ethnic solidarity in Indonesia becomes data to see the potential of traditional sports as supporting identity and how to respect differences. For this reason, views and theories about identity are elaborated in order to explore the extent to which identity is empowered, and explain complex substantive of relationships between person and society. This article is a form of concern for the integrity of NKRI and the attitude of nationalism from a sports and cultural perspective. Thus, an interdisciplinary formula in discussing one subject matter will give more flexible solution of it.